Barriers to Online Shopping - Stojanov, Michal; Grozdeva, Desislava (Research Papers, 2023)
The EU's Digital Single Market Strategy relies on policies to increase opportunities and uniform rules for a seamless and guaranteed through transparent and equal conditions for all market participants for the free exchange of products and the movement of goods, people, services, capital and data. This is applicable regardless of whether the product exchange takes place in a real (physical) or digital environment. The migration to online sales is fraught with problems and barriers. Their study and understanding the genesis of their possible origin allows formulating alternative solutions for their possible overcoming. The paper reviews the data systematized by Eurostat by individual member states for reasons why individuals do not shop on the Internet and analyzes various dimensions of their manifestation and a possible solution.
Keywords: Information society; E-commerce; Information and communication technologies; Online shopping